Sustainable approach in recycling of phase components of large scale aqueous two-phase flotation for lipase recovery - Sankaran, Revathy; Show, Pau Loke; Yap, Yee Jiun; Lam, Hon Loong; Ling, Tau Chuan; Pan, Guan Ting; Yang, Thomas C.K. (Elsevier, 2018)
Recently, aqueous two-phase flotation system has become a powerful method for separation of biomolecules. However, the application of this technique for large scale operation elevates a concern on the environmental issue. This is due to the large amount of chemical consumption for phase components formation. Recycling of hydrophilic organic solvent and inorganic salt in aqueous two-phase flotation is an efficient and green technique for biomolecules recovery. Up to date, there is limited research concerning the recycling of the phase components. In this present work, recycling capability of pilot scale aqueous two-phase flotation composing alcohol/salt was employed to separate lipase from fermentation broth. The drive of this research is to economize the usage of chemicals, to reduce environmental pollution and to establish this approach for sustainable recovery of lipase. The aqueous two-phase flotation system investigated was composed of 1-propanol and ammonium sulphate whereby both phase components went through complete recycling process. Recycling of entire phase components is found to be a sustainable approach as it able to reduce the consumption of chemicals and it is an eco-friendly technique. From the result obtained, it was exhibited that by reusing the bottom phase, separation efficiency was sustained beyond 70%. As for the lipase yield, 80% of yield was achieved from recycling the crystallized salt that was recovered by dilution crystallization with methanol.